2014
DOI: 10.1371/journal.pone.0086243
|View full text |Cite
|
Sign up to set email alerts
|

The Negatively Charged Regions of Lactoferrin Binding Protein B, an Adaptation against Anti-Microbial Peptides

Abstract: Lactoferrin binding protein B (LbpB) is a bi-lobed membrane bound lipoprotein that is part of the lactoferrin receptor complex in a variety of Gram-negative pathogens. Despite high sequence diversity among LbpBs from various strains and species, a cluster of negatively charged amino acids is invariably present in the protein’s C-terminal lobe in all species except Moraxella bovis. The function of LbpB in iron acquisition has yet to be experimentally demonstrated, whereas in vitro studies have shown that LbpB c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
0
40
1
Order By: Relevance
“…The presence of large clusters of negatively charged residues in the LbpB C-lobe from from N. meningitidis and M. catarrhalis led us to propose that these proteins would be involved in protection against lactoferricin H (an 11 residue peptide representing lactoferrin peptides released from human Lf) which was experimentally demonstrated (Morgenthau et al 2012). Subsequent experiments demonstrated that the protection with the meningococcal LbpB was associated with the clusters of negatively charged residues and that this protection extended to other cationic antimicrobial peptides (CAPs), including mouse cathelicidin related antimicrobial peptide (mCRAMP) (Morgenthau et al 2014a;Morgenthau et al 2014b). In this study we demonstrate that protection is extended to extracts from both human and mouse neutrophils (Figures III and IV) that would contain CAPs such as CRAMP and CAPs released by proteolysis D r a f t of Lf.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The presence of large clusters of negatively charged residues in the LbpB C-lobe from from N. meningitidis and M. catarrhalis led us to propose that these proteins would be involved in protection against lactoferricin H (an 11 residue peptide representing lactoferrin peptides released from human Lf) which was experimentally demonstrated (Morgenthau et al 2012). Subsequent experiments demonstrated that the protection with the meningococcal LbpB was associated with the clusters of negatively charged residues and that this protection extended to other cationic antimicrobial peptides (CAPs), including mouse cathelicidin related antimicrobial peptide (mCRAMP) (Morgenthau et al 2014a;Morgenthau et al 2014b). In this study we demonstrate that protection is extended to extracts from both human and mouse neutrophils (Figures III and IV) that would contain CAPs such as CRAMP and CAPs released by proteolysis D r a f t of Lf.…”
Section: Discussionmentioning
confidence: 56%
“…For the alternate model that has been proposed (Noinaj et al 2013), which involves the Lf C-lobe, other bacterial components would have to be invoked in order to explain the positive selection analysis results that primarily impact the Lf N-lobe. These could potentially include the PspA protein from Streptococcus (Shaper et al 2004) and the negatively charged regions of the LbpB C-lobe (Morgenthau et al 2014a), although it is difficult to envision how the latter could confer species specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It affects hemostasis by reducing the time of clot formation, and prevents platelet aggregation (Brock, 2002). Its anti-inflammatory properties are also linked to the ability to bind components of bacterial cell walls (LPS) as well as the specific receptors (Morgenthau, Beddek, Schryvers, 2014). Lipopolysaccharides, potent mediators of the inflammatory response, cause the activation of leukocytes which results in the hyperproduction of free radicals.…”
Section: Antiparasitic Properties Of Lactoferrinmentioning
confidence: 99%